Regulation of T-cell antigen receptor signalling by Syk tyrosine protein kinase. - Latour, S (1997)
T-cell antigen receptor (TCR) signalling has been shown to involve two classes of tyrosine protein kinases: the Src-related kinases p56(lck) and p59(fyr), and the Zap-70/Syk family kinases. Lck and FynT are postulated to initiate TCR-triggered signal transduction by phosphorylating the CD3 and zeta subunits of the TCR complex. This modification permits the recruitment of Zap-70 and Syk, which are presumed to amplify the TCR-triggered signal, by phosphorylating additional intracellular proteins. While Zap-70 is expressed in all T cells, Syk is present in thymocytes and mature T-cell populations such as intraepithelial gammadelta T cells and naive alphabeta T cells. To better understand the role of Syk in these cells, its impact on the physiology of an antigen-specific T-cell line was tested. Our results showed that compared to Zap-70 alone, Syk was a strong positive regulator of antigen receptor-induced signals in BI-141 cells. Surprisingly, they indicated that, like Src family kinases, Syk augmented TCR-triggered tyrosine phosphorylation of CD3/zeta. Syk, but not Zap-70 alone, could also stimulate tyrosine phosphorylation of a zeta-bearing chimera in transiently transfected Cos-1 cells. Finally, evidence was provided that Syk has the capacity to directly phosphorylate a zeta-derived peptide in vitro. These findings suggested that Syk may have a unique role in T cells, as a consequence of its ability to efficiently phosphorylate multiple components of the TCR signalling cascade. Furthermore, they raised the possibility that Syk can regulate the initiation of TCR signalling, by promoting phosphorylation of the immunoreceptor tyrosine-based activation motifs of the TCR complex.